Peran Director of Photography dalam Film Dokumenter “Sehelai Kain Harapan” dengan Penerapan Teknik Sinematografi - Fajar Rizky Dwi Putra; Teddy K. Wirakusumah; Nurmaya Prahatmaja (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
‘Sehelai Kain Harapan’ is a documentary film that discusses the training of batik making by people with disabilities at Pusyansos Griya Harapan Difabel and the formation of a business Batik Griya Difabel. The making of this documentary video does not escape the process of applying cinematographic techniques by a DoP. Therefore, the task of a Director of Photography so that the message to be conveyed can be conveyed properly is carried out the preparation of cinematographic techniques. The purpose of this writing is to find out the application of cinematographic techniques including framing, shot size, camera angle, and camera movement in the production of documentary videos. The stages of creation include pre-production, production, and post-production. Cinematography techniques in the production of this documentary video are carried out to support the delivery of messages and according to the needs of visual narratives in order to be able to build emotions, strengthen the character of subjects and convey messages effectively. The shooting carried out include; opening, interview with the head of the centre, batik making process, interview craftsmen, craftsmen's challenges, coordinator interview, hopes coordinator and closing. The conclusion of this writing is that the activities of applying framing techniques, shot size, camera angle and camera movement in documentary production have been done well.